(untitled) (Revista Brasileira Multidisciplinar, 2025)
The study addresses the analysis of the impact of COVID-19 on medication spending in an ICU in Manaus/AM. This is a cross-sectional and retrospective study using data from medication use reports and hospital indicators for the months of January and February 2020, 2021 and 2022. The ABC Curve was performed on medication consumption and classification of total amounts spent by group main anatomical (ATC classification) and by medication. During the 2nd wave of COVID-19 (2021), beds increased by 244% and care increased by 139%, reflecting an 841% expenditure on medicines compared to the same period in 2020. In 2022, with the vaccine available, the number of cases of COVID-19 increased by 20%, but spending on medicines in the ICU reduced by 85.2%. Medications related to the Nervous System were the most consumed during the months of the study, highlighting fentanyl and medications listed as intubation kits, classified among those of greatest economic relevance. Data analysis confirms that care for patients with COVID-19 had an impact on medication spending, highlighting that management methods such as the ABC Curve can direct the manager to plan inventory more precisely even in the face of a health crisis with the COVID-19 pandemic.